Produktivitas Sapi Potong pada Kelompok Tani Ternak di Pedesaan - Akhmad Sodiq; Machfudin Budiono (Agricultural Faculty, 2012)
Beef Cattle Productivity under Group of Farmer at the VillageABSTRACT. Development of beef cattle in Indonesia should be carried out through sustainable production system approach especially under smallholders in the village areas. The information of beef cattle productivity level under current production system is very important for the basis data in relation to the development strategic program. The purpose of current study was to find out the productivity of beef cattle production under group of farmer at the village areas. Survey method at 34 farmer groups of beef cattle located at Cilacap, Banyumas, Purbalingga, Banjarnegara and Kebumen regencies of Central Java was implemented. The beef catle productivity in terms of cow-calf operation and fattening were recorded. Data analysis by qualitative and quantitative descriptive statistics. This study found that Ongole Cross, Sumba Ongole Cross, Simental Cross and Charolois Cross were raised for fattening and Brahman Cross for cow-calf operation. The performance of beef cattle of fattening purposes was moderate condition. Body Condition Score (BCS) ranged from 4 to 6 (scale 1-9) with the modus 4 (for Ongole Cross, Sumba Ongole Cross) and 5 (for Simental Cross and Charolois Cross). The productivity of cow-calf operation was very low with the reproductive rate and preweaning calf mortality were 6 and 25 percent, respectively. Good Farming Practice with attention on selection of breeds and strengthens feeding aspects could be taking into account in order to improve beef cattle productivity under group of farmer at the village areas.